Reanalysis of semantically required dependents as complements in the Chinese ba-construction - Lipenkova, Janna (Proceedings of the 18th International Conference on Head-Driven Phrase Structure Grammar, 2011)
The paper aims at a formulation of semantic constraints on the produc-tivity of the Chinese ba-construction and their representation at thesyntax-semantics interface. It builds on the observation that requirementson the surface form of the construction may be altered by the choice ofthe verb. I propose that the semantics of the ba-construction can betreated in terms of a scalar constraint: a ba-sentence must come with ascale and a difference value that holds of the described event. Thesatisfaction of this constraint largely relies on the lexical semantics ofthe sentence. Not all verbs are inherently associated with scalarrelations; those that are not must combine with an additional dependentwhich satisfies the scale requirement. Due to the obligatory presence ofthe additional dependent for some verbs, it is reanalyzed as a complementof ba: being optional on their level of combination with the verb, itbecomes obligatory once the verb is used in the ba-construction.